Maternal Perceptions About Sensory Interventions in the Neonatal Intensive Care Unit: An Exploratory Qualitative Study - Lisle, Julia; Buma, Kylie; Smith, Joan; Richter, Marinthea; Satpute, Prutha; Pineda, Roberta (Frontiers in Pediatrics, 2022)
Background: Mothers play an important role in providing positive sensory experiences to their infants during NICU hospitalization. However, little is known about maternal perceptions about sensory-based interventions in the NICU. Further, understanding maternal perceptions was an important part of the process during development of the Supporting and Enhancing NICU Sensory Experiences (SENSE) program. Methods: Twenty mothers of very preterm infants were interviewed after NICU discharge and asked open-ended questions about sensory-based interventions they performed in the NICU and probed about their perceptions related to the development of a sensory-based guideline and the use of volunteers to provide sensory-based interventions when unable to be present in the NICU. Interviews were transcribed and uploaded into NVivoV.12 for content analysis. Results: Mothers reported a common sensory intervention performed in the NICU to be kangaroo care. Of the 18 mothers who commented on the development of a sensory-based guideline, 17 (94%) said they would be accepting. Among 19 mothers, 18 (95%) supported volunteers conducting sensory-based interventions in their absence. Identified themes included: 1) Perceptions about Development of a Sensory-based Guideline, 2) Perceptions of Interactions with Healthcare Providers, 3) Maternal Participation in Sensory Interventions, 4) Maternal Experience, and 5) Emotions from Mothers. Conclusion: Maternal perceptions regarding the development of a sensory-based guideline were favorable, and the SENSE program has since been finalized after incorporating important insights learned from stakeholders in this study. Mothers’ perceptions were tied to their NICU experiences, which elicited strong emotions. These findings highlight important considerations when developing family-centered interventions.